2021
DOI: 10.1038/s41438-021-00656-2
|View full text |Cite
|
Sign up to set email alerts
|

D6 protein kinase in root xylem benefiting resistance to Fusarium reveals infection and defense mechanisms in tung trees

Abstract: Fusarium oxysporum, a global soil-borne pathogen, causes severe disease in various cultivated plants. The mechanism underlying infection and resistance remains largely elusive. Vernicia fordii, known as the tung tree, suffers from disease caused by F. oxysporum f. sp. fordiis (Fof-1), while its sister species V. montana displays high resistance to Fof-1. To investigate the process of infection and resistance ability, we demonstrated that Fof-1 can penetrate the epidermis of root hairs and then centripetally in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The gene g000 (Chr0) has a functional annotation for serine/threonine-protein kinase D6PKL2. In Zhang et al. (2021) this protein was described as specifically expressed after Fusarium oxysporum infection in Vernicia montana resistant trees.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The gene g000 (Chr0) has a functional annotation for serine/threonine-protein kinase D6PKL2. In Zhang et al. (2021) this protein was described as specifically expressed after Fusarium oxysporum infection in Vernicia montana resistant trees.…”
Section: Discussionmentioning
confidence: 99%
“…The gene g000 (Chr0) has a functional annotation for serine/threonine-protein kinase D6PKL2. In Zhang et al (2021) this protein was described as specifically expressed after Fusarium oxysporum infection in Vernicia montana resistant trees. Furthermore, transgenic analysis in Arabidopsis and tomato revealed that D6PKL2 significantly enhanced resistance in both species, whereas the d6pkl2 mutant displayed reduced resistance against F. oxysporum (Zhang et al, 2021).…”
Section: Identification Of Candidate Genes Related To Plant Defense T...mentioning
confidence: 99%
See 1 more Smart Citation